Rancang Bangun Sistem Informasi Akuntansi Keuangan Pada Lembaga Manajemen Zakat Infaq Dan Shadaqah - Paramitha, Tika; Widodo, Arifin Puji; Sutanto, Teguh (Jurnal JSIKA, 2012)
Lembaga Manajemen Infaq dan shadaqah (LMZIS) is an institution which is engaged in social and propagation, such as collecting Zakat, Sadaqah infaq and Muslims in the ITS, alumni and the surrounding communities. In the implementation LMZIS notimplement a system of financial accounting information is good, one of which was not reported for managerial accountability to the public. In addition the management has not been able to evaluate the performance of the activity in each month. Given the existing problems in LMZIS, it is necessary to the existence of a financialaccounting information systems that produce financial information that is derived fromactivity data per period and the data resulting in donor funds that are transparentmanagerial reports such as financial reports, evaluation reports and other reports. It can facilitate the directors, muzzaki and donors to get clear information. Based on the results of experiments performed can be concluded that, the system of financial accounting information on LMZIS can help existing business processes incurrent LMZIS start of the process of recording transactions, financial reporting, andevaluation. So that the output generated by the system are made to solve the problems faced by LMZIS today. Keywords: ZIS, Financial Statements, Report of managerial, Accounting